BIOCHEMICAL AND ULTRASTRUCTURAL ASPECTS OF CA(2+) TRANSPORT BY MITOCHONDRIA OF THE HEPATOPANCREAS OF THE BLUE CRAB CALLINECTES SAPIDUS - Chen, Chung-Ho (The Rockefeller University Press, 1974)

(untitled)
Mitochondria isolated from the hepatopancreas of the blue crab Callinectes sapidus show up to 12-fold stimulation of respiration on addition of Ca(2+), which is accompanied by Ca(2+) accumulation (Ca(2+):site = 1.9) and H(+) ejection (H(+):Ca(2+) = 0.85). Sr(2+) and Mn(2+) are also accumulated; Mg(2+) is not. A strongly hypertonic medium (383 mosM), Mg(2+), and phosphate are required for maximal Ca(2+) uptake. Ca(2+) uptake takes precedence over oxidative phosphorylation of ADP for respiratory energy. Once Ca(2+) is accumulated by the crab mitochondria, it is stable and only very slowly released, even by uncoupling agents. ATP hydrolysis also supports Ca(2+) uptake. Respiration-inhibited crab hepatopancreas mitochondria show both high-affinity and low-affinity Ca(2+)-binding sites, which are inactive in the presence of uncoupling agents. Crab hepatopancreas mitochondria have an enormous capacity for accumulation of Ca(2+), up to 5,500 ng-atoms Ca(2+) per mg protein, with an equivalent amount of phosphate. Freshly isolated mitochondria contain very large amounts of Ca(2+), Mg(2+), phosphate, K(+), and Na(+); their high Ca(2+) content is a reflection of the vary large amount of extra-mitochondrial Ca(2+) in the whole tissue. Electron microscopy of crab mitochondria loaded with Ca(2+) and phosphate showed large electron-dense deposits, presumably of precipitated calcium phosphate. They consisted of bundles of needle-like crystals, whereas Ca(2+)-loaded rat liver mitochondria show only amorphous deposits of calcium phosphate under similar conditions. The very pronounced capacity of crab hepatopancreas mitochondria for transport of Ca(2+) appears to be adapted to a role in the storage and release of Ca(2+) during the molting cycle of this crustacean.